Evidence that the Arabidopsis nuclear gibberellin signalling protein GAI is not destabilised by gibberellin. - Fleck, B; Harberd, N (2002)
Plant growth is regulated by bioactive gibberellin (GA), although there is an unexplained diversity in the magnitude of the GA responses exhibited by different plant species. GA acts via a group of orthologous proteins known as the DELLA proteins. The Arabidopsis genome contains genes encoding five different DELLA proteins, the best known of which are GAI and RGA. The DELLA proteins are thought to act as repressors of GA-regulated processes, whilst GA is thought to act as a negative regulator of DELLA protein function. Recent experiments have shown that GA induces rapid disappearance of nuclear RGA, SLR1 and SLN1 (DELLA proteins from rice and barley), suggesting that GA signalling and degradation of DELLA proteins are coupled. However, RGL1, another Arabidopsis DELLA protein, does not disappear from the nucleus in response to GA treatment. Here, we present evidence suggesting that GAI, like RGL1, is stable in response to GA treatment, and show that transgenic Arabidopsis plants containing constructs that enable high-level expression of GAI exhibit a dwarf, GA non-responsive phenotype. Thus, GAI appears to be less affected by GA than RGA, SLR1 or SLN1. We also show that neither of the two putative nuclear localisation signals contained in DELLA proteins are individually necessary for nuclear localisation of GAI. The various DELLA proteins have different properties, and we suggest that this functional diversity may explain, at least in part, why plant species differ widely in their GA response magnitudes.